2021
DOI: 10.5755/j02.ms.23557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laser Scanning Speed on Microstructure and Performance of Cr3C2-NiCr Cermet Fabricated by in-situ Laser Cladding

Abstract: To explore the effect of laser scanning speed on the microstructure and performance of Cr3C2-NiCr cermet layers fabricated by in-situ laser cladding, Cr3C2-NiCr cermet layers were laser cladded from Ni/Cr/Graphite (25:65:10 wt.%) elemental powder mixtures. The microstructures of the laser cladded cermet layers and the formation mechanism were investigated. In addition, the effect of laser scanning speed on the microstructure, friction and corrosion performance of the Cr3C2-NiCr cermet layers was studied. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Cr 3 C 2 -NiCr cermet coating is prepared by wrapping Cr 3 C 2 with NiCr, which greatly improves the mechanical properties of the material. The hardness of the Cr 3 C 2 hard phase and the toughness of the NiCr adhesive phase are both improved [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cr 3 C 2 -NiCr cermet coating is prepared by wrapping Cr 3 C 2 with NiCr, which greatly improves the mechanical properties of the material. The hardness of the Cr 3 C 2 hard phase and the toughness of the NiCr adhesive phase are both improved [21].…”
Section: Introductionmentioning
confidence: 99%
“…The cooling rate determined by the laser beam scan speed had an additional effect in reducing the carbide content in laser clad layers. Lou et al [21] studied the microstructure and formation mechanism of a laser cladding cermet layer, and they found that the laser scanning velocity had a significant effect on carbide content. The solidification rate of the metal molten pool increased, while the size of carbides decreased with the increase in the scanning speed.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, laser cladding Ni60 composite coating can significantly improve the wear resistance of the substrate material surface to meet the performance requirements of the material surface [5,6]. Nevertheless, high stress and cracks are generated in the cladding layer due to the rapid cooling and heating of laser cladding [7,8]. Due to the characteristics of rare earth grain refinement to inhibit cracking, it has been successfully applied in the field of laser cladding [9,10].…”
Section: Introductionmentioning
confidence: 99%